Lung Volume Reduction in Pulmonary Emphysema - Garner, Justin L.; Shah, Pallav L. (Seminars in Respiratory and Critical Care Medicine, 2020)
Severe emphysema with hyperinflation presents a therapeutic challenge. Inhaled medication has limited efficacy in individuals with mechanical constraints to the respiratory pump and impaired gas exchange. Lung volume reduction surgery (LVRS) reestablishes some semblance of normal physiology, resecting grossly expanded severely diseased tissue to restore the function of compromised relatively healthy lung, and has been shown to significantly improve exercise capacity, quality of life, and survival, especially in individuals with upper-lobe predominant emphysema and low-baseline exercise capacity, albeit with higher early morbidity and mortality. Bronchoscopic lung volume reduction achieved by deflating nonfunctioning parts of the lung is promoted as a less invasive and safer approach. Endobronchial valve implantation has demonstrated comparable outcomes to LVRS in selected individuals and has recently received approvals by the National Institute of Clinical Excellence in the United Kingdom and the Food and Drug Administration in the United States of America. Endobronchial coils are proving a viable treatment option in severe hyperinflation in the presence of collateral ventilation in selected cases of homogeneous disease. Modalities including vapor and sealant are delivered using a segmental strategy preserving healthier tissue within the same target lobe-efficacy and safety-data are, however, limited. This article will review the data supporting these novel technologies.
Keywords: chronic obstructive pulmonary disease; lung volume reduction; pulmonary emphysema